ITO‐Free Organic Photovoltaic Modules Based on Fluorinated Polymers Deposited from Non‐Halogenated Solution: A Major Step Toward Large‐Scale Module Production. Issue 12 (27th August 2019) - Ibraikulov, Olzhas. A.; Wang, Jing; Kamatham, Narayanaswamy; Heinrich, Benoît; Méry, Stéphane; Kohlstädt, Markus; Würfel, Uli; Ferry, Stéphanie; Leclerc, Nicolas; Heiser, Thomas; Lévêque, Patrick
Abstract : Several bottlenecks need to be passed to reach market readiness for organic photovoltaic modules. To avoid scarce and costly materials such as indium is an important technological issue. To be able to process the active layer from solutions prepared from non‐halogenated solvents and harmless additives is also a crucial step. Herein, a fluorinated polymer is used as an electron‐donor material and PC71 BM as an electron‐accepting material in a bulk‐heterojunction configuration, to demonstrate that indium‐tin‐oxide (ITO)‐free modules with an active area greater than 60 cm 2 and processed from non‐halogenated solvents and harmless additives can reach a high power conversion efficiency of above 6%. Abstract : A blend of a fluorinated polymer and PC71 BM composes the photoactive layer of a bulk‐heterojunction photovoltaic module. Using non‐halogenated solvents and harmless additives as well as an ITO‐free architecture, a power conversion efficiency of above 6% is obtained. This is an important step to reach market readiness for organic photovoltaic modules.